A83 BEST PRACTICES FOR THE PROVISION OF VIRTUAL CARE IN IBD AND BEYOND: A SYSTEMATIC REVIEW OF CURRENT GUIDELINES. (21st February 2022) - Anvari, S; Neumark, S; Jhangra, R; Sandre, A; Pasumarthi, K; Xenodemetropoulos, T
Abstract: Background: Telemedicine has emerged as a feasible adjunct to in-person care in multiple clinical contexts, including inflammatory bowel disease (IBD), and its role has expanded in the context of the COVID-19 pandemic. However, there exists a general paucity of information surrounding best practice recommendations for conducting specialty or disease-specific virtual care. Aims: The purpose of this study was to systematically review existing best practice guidelines for conducting telemedicine encounters, both in general and specific to patients with IBD. Methods: A systematic review of MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) of existing guidelines for the provision of virtual care was performed. Data was synthesized using the Synthesis Without Meta-Analysis (SWiM) guideline, and the AGREE II tool was used to evaluate quality of evidence Results: A total of 60 studies providing guidance for virtual care encounters were included; 52% of these were published during the COVID-19 pandemic. No gastroenterology-specific guidelines were found. The majority (95%) of provider guidelines specified a type of virtual encounter to which their guidelines applied. Of included studies, 65% provided guidance regarding confidentiality/security, 58% discussed technology/setup, and 56% commented on patient consent. 31 studies also provided guidance to patients or caregivers. Overall guideline quality was poor. Conclusions: General best practices for successful telemedicine encounters include ensuring confidentiality and consent, preparation prior to a visit, and clear patient communication. Future studies should aim to objectively assess the efficacy of existing clinician practices in order to further optimize the provision of virtual care for specific populations, such as patients with IBD. Funding Agencies: None